AGENCY REPRESENTATIVE APPLICATIONS WEBSITE DESIGN STUDENTS STMIK JAKARTA STI & K USING PHP & MYSQL - Caryadi Caryadi; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Media information is a means to convey a message or information that we received, both orally and in writing, and various kinds such as newspapers, television, radio and computers.Internet is one medium of information very quickly. The required information must be information very quickly, accurately, and can be accounted for authenticity. Student Representative Body (BPM) is one of the student information centerand aspirations STMIK JakartaSTI & K. For the implementation can be used server side scripting programming language PHP (Personal Home Page) for information on the site can be accessed through the Internet and utilize the MySQL software so that the contents of the site more interesting and dynamic. With the expected student BPM website STMIK Jakarta  STI&K  can  get  information  and  channel  their  aspirations